Bilateral Pulmonary Embolism in a 12-Year-Old Girl with Steroid-Resistant Nephrotic Syndrome - Osama Y. Safdar; Rahaf H. Rajab; Rand G. Alghanemi; Gazal A. Tantawi; Noora A. Alsulami; Aeshah A. Alsayed; Abdullah K. Habiballah (MDPI AG, 2020)
Nephrotic syndrome is the most common glomerular disease among children. Although most cases respond to steroid therapy, approximately 10-20% of patients exhibit resistance to conventional steroid therapy and are labeled as steroid-resistant. Such patients are at risk of complications, including infection, thrombosis, and chronic kidney disease. Nephrotic syndrome is considered a thrombogenic condition. Pulmonary embolism is associated with high mortality, and early treatment is essential for the survival of patients. Here, we report the case of a 12-year-old girl with late steroid resistance who developed bilateral pulmonary embolism.